STRATEGIES FOR OVERCOMING DIFFICULTIES IN LEARNING SCIENCE IN CLASS III AT PRIMARY SCHOOL JRUEK ACEH BESAR - Mughni Mughni 'Alya; Siti Mayang Sari (SENSEI RESEARCH CENTER, 2024)
Education in Indonesia plays a central role in forming the basic knowledge and skills of students. In the context of an increasingly complex basic education curriculum, Natural Sciences (IPA) is a crucial subject. Science not only presents scientific concepts, but also involves students in scientific thinking, observation and exploration. In facing learning challenges, especially in grade III of the Jruek Aceh Besar State Elementary School, where difficulties in learning science arise, effective strategies are needed. This research aims to explore the strategies implemented in this school to overcome science learning difficulties. This research uses a qualitative approach with descriptive research type. Based on the results of the interview, it can be seen that the third grade teacher at the Jruek Aceh Besar Elementary School identified that some students had difficulty learning science. This assessment becomes the basis for designing adaptive teaching strategies, involving students in interactive activities, such as project-based approaches and the use of learning media. Factors causing learning difficulties involve the complexity of the material, differences in student learning styles, lack of parental support, limited learning infrastructure, and students' psychological conditions. It is hoped that parental involvement in school activities will have a positive impact on the learning achievement of class III students at the Jruek Aceh Besar Public Elementary School.